Coaching instrucional: uma experiência promissora para a formação continuada em serviço de professores de línguas estrangeiras - Alex Garcia da Cunha (2014)
This qualitative-oriented study aimed to investigate instructional coaching (Barkley, 2005; Knight, 2004, 2005, 2006, 2007, 2009) as an approach to in-service continuing education for English language teachers in Brazil by analyzing the experiences of a public school teacher who sought to implement Communicative Language Teaching (Richards, 2006) into her classes with the collaboration of an instructional coach. The teacher had low communicative performance in English as well as a teaching approach grounded in grammar-translation. Instructional coaching and data collection took place from March 2012 to February 2013 through audio recordings, semi-structured interviews, questionnaires and document related to the study. Data analysis was carried out based on the construct of experience (Gelter, 2010; Miccoli, 1997, 2010). The results showed that the instructional coaching partnership assisted the teacher to develop her teaching approach as well as her performance in English. In addition, instructional coaching contributed to the improvement of teacher-student interaction. The study highlights the necessity of more qualified foreign language teachers in Brazil and suggests instructional coaching as an effective approach to in-service continuing education.